Stability of proICA512/IA-2 and its targeting to insulin secretory granules require β4-sheet-mediated dimerization of its ectodomain in the endoplasmic reticulum - Torkko, Juha M. (2015)
The type 1 diabetes autoantigen ICA512/IA-2/RPTPN is a receptor protein tyrosine phosphatase of the insulin secretory granules (SGs) which regulates the size of granule stores, possibly via cleavage/signaling of its cytosolic tail. The role of its extracellular region remains unknown. Structural studies indicated that β2- or β4-strands in the mature ectodomain (ME ICA512) form dimers in vitro. Here we show that ME ICA512 prompts proICA512 dimerization in the endoplasmic reticulum. Perturbation of ME ICA512 β2-strand N-glycosylation upon S508A replacement allows for proICA512 dimerization, O-glycosylation, targeting to granules, and conversion, which are instead precluded upon G553D replacement in the ME ICA512 β4-strand. S508A/G553D and N506A/G553D double mutants dimerize but remain in the endoplasmic reticulum. Removal of the N-terminal fragment (ICA512-NTF) preceding ME ICA512 allows an ICA512-ΔNTF G553D mutant to exit the endoplasmic reticulum, and ICA512-ΔNTF is constitutively delivered to the cell surface. The signal for SG sorting is located within the NTF RESP18 homology domain (RESP18-HD), whereas soluble NTF is retained in the endoplasmic reticulum. Hence, we propose that the ME ICA512 β2-strand fosters proICA512 dimerization until NTF prevents N506 glycosylation. Removal of this constraint allows for proICA512 β4-strand-induced dimerization, exit from the endoplasmic reticulum, O-glycosylation, and RESP18-HD-mediated targeting to granules.